2017
DOI: 10.1371/journal.pone.0177131
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric detection of melamine in milk by using gold nanoparticles-based LSPR via optical fibers

Abstract: A biosensing system with optical fibers is proposed for the colorimetric detection of melamine in liquid milk samples by using the localized surface plasmon resonance (LSPR) of unmodified gold nanoparticles (AuNPs). The biosensing system consists of a broadband light source that covers the spectral range from 200 nm to 1700 nm, an optical attenuator, three types of 600 μm premium optical fibers with SMA905 connectors and a miniature spectrometer with a linear charge coupled device (CCD) array. The biosensing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This method showed a LOD at picogram level, and hence such design is highly desirable. The BSA conjugated Au NPs were Aggregation and electrostatic forces involved tactics were also described by a few reports [122,134,144,154,158]. However, these methodologies still require more attention.…”
Section: Nanoparticles In Melamine Quantificationmentioning
confidence: 93%
“…This method showed a LOD at picogram level, and hence such design is highly desirable. The BSA conjugated Au NPs were Aggregation and electrostatic forces involved tactics were also described by a few reports [122,134,144,154,158]. However, these methodologies still require more attention.…”
Section: Nanoparticles In Melamine Quantificationmentioning
confidence: 93%
“…In a preliminary study of the practical applications in food contents analysis, the sugar contents in three different commercial juices were measured ( Figure 13 b), and it was confirmed that the sensor has the potential to be applied to the analysis of ingredients for food or beverages. Chang et al [ 114 ] developed a fiber-optic LSPR colorimetric sensor to detect melamine in milk samples. The fiber-optic melamine sensor was based on the sensitivity improvement by the LSPR derived from unmodified gold nanoparticles.…”
Section: Recent Studies Of Fiber-optic Localized Surface Plasmon Rmentioning
confidence: 99%
“…Various analytical methods have been used in the determination of MEL in dairy products such as high performance liquid chromatography (HPLC)-UV detection (HPLC-UV) [26][27][28] or -tandem mass spectrometry (LC-MS/MS) [29][30][31] . And the hydrophilic interaction liquid chromatography (HILIC) 32 , surface-enhanced Raman spectroscopy (SERS) 33 and surface plasmon resonance (SPR) 34 suspension with the protection of N 2 flow and stirred for min. Then the core/shell nano particle of Fe O 4 @Polyrutine-COOH was accepted easily with an external magnetic field.…”
Section: Analytical Sciencesmentioning
confidence: 99%